Report on vocational education and training 2014 - (:unkn) unknown (My University, 2014)
The "Report on Vocational Education and Training 2014" was adopted by the Federal Cabinet in its meeting on 8 April 2014. It offers a large overview of the training market situation in 2013 and contains a prognosis on the development of the 2014 training year. The Report points out that the German dual system approach is internationally more and more seen as a model of success. But is not denied that several challenges are lying ahead of us, such as the demographic change and the increasing number of young people who decide to study instead of starting an apprenticeship. (BIBB-Doku)
Dt. Ausg. u.d.T.: Berufsbildungsbericht 2014
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.1.1 Ausbildungsstellenmarkt; T 3.5 Statistik; S 2.3.2 Programme in der Berufsbildung; Berufsbildungsbericht; Ausbildungsstellenmarkt; Berufsbildungsstatistik; Berufsbildungspolitik; Programm; Duales System; Benachteiligtenförderung; Übergangssystem; Berufliche Weiterbildung; Durchlässigkeit im Bildungssystem; Internationale Zusammenarbeit; 2013